Developing Management Information System for Teachers and Education Staff - Hendri Murti Susanto; Willem Mantja; Ibrahim Bafadal; Ahmad Sonhadji (Pascasarjana UM, 2015)
Pengembangan SIM Pendidik dan Tenaga KependidikanAbstract: This study aims to: (1) Build a model school information data processing and management information system; (2) find the specifications of software, hardware, and brainware that suit the needs, and (3) Information System of Teachers and Education Personnel Integrated (SI-PINTER). This study uses a descriptive model of development, namely the development of framework approach- end-user development, and using testing phases of a product by combination trials of Borg and Gall. The program specification software is using fourth generation tools technique. The test is done to look at the effectiveness, efficiency and attractiveness of the product. The data in this qualitative test contains discussions and black box testing; as well as quantitative data from the questionnaire and field test. Experimental results show the effectiveness and maximum efficiency of the SI-PINTER, as well as the ability to triangulate the data generated by the 3 modules. Key Words: management information systems, educators and education personnel, vocational high schoolsAbstrak: Penelitian ini bertujuan untuk: (1) membangun model proses pengolahan data informasi sekolah dan Sistem Informasi Manajemen; (2) menemukan spesifikasi software, hardware, dan brain-ware yang sesuai dengan kebutuhan, dan (3) aplikasi Sistem Informasi Pendidik dan Tenaga Ke-pendidikan Terpadu (SI-PINTER). Penelitian ini menggunakan model pengembangan deskriptif, yaitu pengembangan kerangka kerja menggunakan pendekatan end-user development, serta uji coba produk menggunakan kombinasi tahapan uji coba Borg dan Gall. Spesifikasi program software menggunakan teknik fourth generation tools. Uji coba dilakukan untuk melihat tingkat keefektifan, efisiensi dan daya tarik produk yang dihasilkan. Data uji coba ini bersifat kualitatif berisi hasil diskusi dan uji black box; serta data kuantitatif dari hasil kuesioner serta uji lapangan. Hasil uji coba menunjukkan tingkat keefektifan dan efisiensi yang maksimal dari SI-PINTER, serta kemampuan triangulasi data yang dihasilkan oleh 3 modul tersebut.Kata kunci: sistem informasi manajemen, pendidik dan tenaga kependidikan, sekolah menengah kejuruan